From Silence to Systems: A System-Level Response to the Second Victim Crisis - Misty Stone (Quality Management in Health Care, 2026)
Background and Objectives: The second victim phenomenon refers to the emotional and psychological distress experienced by health care professionals following involvement in adverse patient events. Despite increasing awareness, institutional responses remain inconsistent, while support systems are often fragmented or even lacking. This presents significant implications for health care workers’ well-being, patient safety, and organizational culture. This integrative literature review aims to (1) examine the experiences of second victims across health care settings, (2) evaluate current institutional support systems, and (3) propose a conceptual framework to guide more comprehensive and systemic responses to second victim distress. Methods : Guided by Whittemore and Knafl’s integrative review framework, a comprehensive search of PubMed, CINAHL, PsycINFO, and Scopus was conducted for studies published between 2000 and 2024. The PRISMA guidelines were followed to screen and select relevant articles. The methodological quality of the included studies was assessed using the Mixed Methods Appraisal Tool, and findings were synthesized thematically. Results : Eleven studies met the inclusion criteria. Four central themes were identified: (1) emotional and psychological impact, (2) organizational culture and support, (3) coping and help-seeking behaviors, and (4) institutional responses and interventions. A novel conceptual model, The Second Victim Support Ecosystem, was developed to conceptualize the interconnected layers of second victim experiences and organizational responsibilities. Conclusions : Second victim distress is a critical, under-addressed issue that undermines provider resilience and patient safety. While some organizations have implemented promising interventions, a lack of standardization persists. This review introduces a layered conceptual framework and offers actionable recommendations to guide the development of comprehensive, system-level second victim support strategies.